Kamishibai storytelling for sustainability: A community partnership program in elementary schools - Ai Nurhayati; Diana Rochintaniawati; Neti Budiwati; Rita Anggorowati; Hany Handayani (Universitas Pendidikan Indonesia, 2025)
Lembang, West Bandung Regency, Indonesia, has recently faced flooding risks in Cikole Village due to reduced water catchment areas and the conversion of pine forests into tourist sites. This highlights the need to foster environmental awareness from an early age, particularly through elementary school teachers. This Community Service Program (Pengabdian kepada Masyarakat or PkM) aimed to equip 50 elementary teachers in Lembang with knowledge and skills to use Kamishibai as a learning tool to raise student awareness of sustainability issues. The program used a mezzo approach, focusing on strengthening groups through structured workshops that included plenary sessions, small-group practice, presentations, and feedback. The service phase involved preparation, implementation, evaluation, data analysis, and ethics considerations. Reflection data were collected via post-training questionnaires, process observations, and facilitator notes. Results showed significant improvement in teachers’ understanding of sustainability and their ability to design and use Kamishibai effectively in classrooms. Teachers found Kamishibai engaging, easy to use, and helpful in simplifying environmental concepts for students. The mezzo approach also strengthened teachers’ collective capacity as change agents. This program offers a valuable model for enhancing elementary environmental education, with the potential to be replicated through ongoing mentoring to ensure lasting impact. Abstrak Kecamatan Lembang, Kabupaten Bandung Barat, Indonesia merupakan wilayah dataran tinggi yang belakangan menghadapi risiko banjir di Desa Cikole akibat berkurangnya daerah tangkapan air dan perubahan fungsi lahan hutan pinus menjadi kawasan wisata. Kondisi ini menegaskan pentingnya menumbuhkan kepedulian lingkungan sejak dini melalui peran guru sekolah dasar. Program Pengabdian kepada Masyarakat (PkM) ini bertujuan membekali guru dengan pengetahuan dan keterampilan menggunakan Kamishibai sebagai media pembelajaran untuk meningkatkan kepedulian murid terhadap isu keberlanjutan. Kegiatan melibatkan 50 guru SD di Kecamatan Lembang dan menerapkan pendekatan mezzo, pendekatan penguatan kelompok agar terjadi transformasi kolektif melalui workshop terstruktur (sesi pleno, praktik kelompok kecil, presentasi-umpan balik). Tahapan pengabdian terdiri dari lima tahapan: persiapan, pelaksanaan, evaluasi kegiatan, analisis data, dan etika kegiatan. Data refleksi dikumpulkan menggunakan angket pasca pelatihan, dilengkapi observasi proses dan catatan fasilitator. Hasil menunjukkan peningkatan pemahaman guru mengenai isu keberlanjutan dan kemampuan merancang serta memanfaatkan Kamishibai secara kontekstual di kelas. Guru menilai Kamishibai menarik, mudah diterapkan, dan efektif menyederhanakan konsep lingkungan bagi murid. Pendekatan mezzo memperkuat kapasitas kolektif guru sebagai agen perubahan di sekolah melalui kolaborasi dan berbagi praktik. Program ini memberikan kontribusi nyata bagi pendidikan lingkungan tingkat dasar dan berpotensi direplikasi dengan dukungan pendampingan lanjutan agar dampak pembelajaran kian berkelanjutan. Kata Kunci: isu berkelanjutan; kamishibai; media pembelajaran; pendekatan mezzo